Quality evaluation of shrimp by-product complete ration pellets - Andi Saenab; Erika B. Laconi; Yuli Retnani; M. Sayuti Mas’ud (Jurnal Ilmu Ternak dan Veteriner, 2010)
This research was done to evaluate the physical characteristic and chemical quality of the complete ration in pellet form that contain shrimp by-product.  The evaluation was done on several variables namely: moisture content, water activity, particle size, average collision endurance, friction endurance and angle of repose. Data obtained was analyzed based on Completely randomized design. The treatment was: R0 (complete ration without shrimps by-product), R1 (complete ration with 10% shrimps by-product), R2 (complete ration with 20% shrimps by-product) and R3 (complete ration with 30% shrimps by-product). The results showed that physical characteristic of the complete ration pellet that contain 20% shrimps by-product had the lowest moisture (13.07%) and the water activity (0.45). Based on the research, it is concluded that the best level of shrimp by-product in the complete ration was 20%. Key words:  By-Product, Pellet, Digestibility, Sheep